A especialização em segurança empresarial para executivos no Rio de Janeiro - Borges, Gerson Antônio de Souza (2002)
The purpose of this study is to indentify specific needs of knowledge for the executive who has a management/direction task in the security area of a company. It presents a model of specialization course which fulfils the needs of these professionals. Considering that such a course is still incipient in Brazil, this study is based on programs existing in American, British, Spanish and Australian universities. Such courses served as model to be adapted to our business reality, to the experiences of security executives in Brazilian companies, and to the reality of our country in terms of corporate security. I intend to develop the structure of a post graduation program in corporate security by means of descriptive and applied research, presenting the history of security, risks and prevention, and security study areas. The resu/ting curricu/um should contempla te management aspects common to any organization, such as finances, human resources, logistics etc. This structure should finally answer specific demands ofBrazilian companies, according to the Brazilian present scenario, considering its social, political, economical and cultural aspects